TECHNOLOGIES OF SOCIOCULTURAL INTEGRATION OF FOREIGN STUDENTS: EXPERIENCE OF THE RUSSIAN-CHINESE EDUCATIONAL COOPERATION - Tatyana L. Guruleva (Высшее образование в России, 2016)
The purpose of the article is to describe the pedagogical technologies of sociocultural integration of foreign students, which are approved in experience of the Russian-Chinese educational cooperation. During the development of the pedagogical technologies, the system method was used as a general scientific method; also were used theoretical methods: analysis, inductive and deductive methods, and empirical methods: supervision, pedagogical experiment. As a result of research two pedagogical technologies of foreign students sociocultural integration are developed: the technology of the personality self-determination in foreign-language society and culture organizing the personal choice of the line item, the purposes and means of self-implementation in new sociocultural conditions; and the technology of pedagogical support the personality for socialization in the foreign language community and acculturation.The second technology is aimed at integration ofthe personality into foreign-language society and culture. Technologies have passed successful approbation in the course of training of the Russian students in the People's Republic of China, and also in training process of the Chinese students in Russia.